Adult onset Still's disease associated with malignancy-Cause or coincidence? - Hofheinz, Katharina; Schett, Georg; Manger, Bernhard (Seminars in Arthritis and Rheumatism, 2016)
To analyze all patients with adult onset Still's disease (AOSD) and malignancy described in the literature and to discuss their relation to each other.Demographic, clinical, and laboratory characteristics of one index patient with AOSD seen in our institution who subsequently developed a malignant disease were compared with all other cases of AOSD and malignancy identified by a PubMed literature research. Furthermore, characteristics of AOSD patients with malignancy were compared to those without malignancy.We found 46 articles in English, French, Japanese, Korean, and Spanish language reporting 47 cases in addition to our own case. In 36 patients, the diagnosis of AOSD could be confirmed by retrospectively applying classification criteria according to Yamaguchi, Fautrel, and Crispin. The median time between diagnosis of AOSD and subsequent detection of a malignant disease was 9 months, 50% had a hematological disorder and 50% a solid tumor. In 33%, the symptoms of AOSD resolved after successful therapy of the neoplastic disease. Red flags for paraneoplastic AOSD were onset of symptoms at higher age, atypical features of rash, highly elevated lactate dehydrogenase, atypical cells in the differential blood count, and high concentrations of the soluble interleukin-2 receptor.A disease resembling AOSD can precede the clinical appearance of a hematologic malignancy or a solid tumor. Thorough diagnostic work-up of AOSD to rule out malignancy and awareness to conspicuous signs for malignancy-associated AOSD are therefore essential in the clinical work-up of such patients.
EVALuna2:13178